2021
DOI: 10.1159/000516232
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Risk Factors Associated with Acne Vulgaris Presentation, Severity, and Scarring in a Singapore Chinese Population: A Cross-Sectional Study

Abstract: <b><i>Background:</i></b> Acne vulgaris is classified based on the severity of skin lesions and post-healing scar types of these lesions. Numerous epidemiology studies have investigated the risk factors associated with acne presentation and severity, but studies for acne scarring are lacking. <b><i>Objective:</i></b> To investigate the prevalence of acne, severity, and scarring grades and their associated risk factors among Singapore Chinese. <b><i>Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 37 publications
1
16
1
Order By: Relevance
“…Data from our previous cross‐sectional study 9 and the current analysis both demonstrated an acne‐protective effect of milk consumption, while other reviews have shown an acne‐promoting effect of milk and dairy product consumption 3,4 9 …”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…Data from our previous cross‐sectional study 9 and the current analysis both demonstrated an acne‐protective effect of milk consumption, while other reviews have shown an acne‐promoting effect of milk and dairy product consumption 3,4 9 …”
Section: Discussionsupporting
confidence: 54%
“…Acne-protective properties of fruits and vegetables could be attributed to their high fibre content, which have been shown to lower the levels of IGF-1, 25 and anti-inflammatory and antioxidant effects of the phytochemicals in them. 26 Data from our previous cross-sectional study 9 and the current analysis both demonstrated an acne-protective effect of milk consumption, while other reviews have shown an acne-promoting effect of milk and dairy product consumption. 3,4 This may be due to the heterogeneity between studies in the assessment of dairy product consumption, which has been discussed previously.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations